Instilling Values and Noble Upbringing Among Members of Society: An Analytical Study in Surah Al-An’am - Al-Saadi, Prof. Dr. Yaqoub Nazim Ahmed Al-Saadi (Sulaimani Journal for Humanities, 2026)
It is agreed upon that the Noble Qur’an was revealed by Allah Almighty to build a society characterized by the highest values and noble social upbringing, and characterized by social awareness. This is clear in the Surahs that contain many verses that explain the ways, principles, and points that clarify how to build a society upon values and Islamic upbringing in light of the Qur’anic instructions. One of the important Surahs is Surah Al-An’am, which includes many regulations, principles, and guidelines for building society, especially the three verses (151, 152, 153) which include the Ten Commandments. These important principles serve to instill values and noble upbringing to build a society characterized by cooperation, progress, and creativity. Among the most important commandments directed to society are: belief in Allah and not associating partners with Him, and what this has of effects on the unity and upbringing of society; obedience to parents, respecting them and serving them; preserving the family and offspring; not assaulting humans by unjust killing; social aspects like aggression against orphans; financial aspects like cheating in weight and measure and the resulting negative consequences; justice and fulfilling covenants and their benefits. All these commandments are the foundations for establishing a society characterized by Islamic upbringing, virtue, and mercy.
Keywords: values; development; society; justice; integrity